A metal-doped catalyst for efficient and selective electrochemical nitrogen reduction of TiO2 and its application.

CN117821996BActive Publication Date: 2026-10-16MINNAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310472789.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2026-10-16
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

但TiO2也存在导电性差、活性位点少的问题

Benefits of technology

[0014] Density functional theory studies further demonstrate that surface oxygen vacancies and newly introduced Fe sites on the Fe-TiO2 surface can effectively lower the nitrogen reduction rate and the energy barrier of the determining step (below the energy barrier of the original TiO2), thereby promoting the catalytic performance of electrocatalytic nitrogen reduction. Fe-doped phase transition engineering, which transforms the TiO2 crystal structure into a single anatase structure, is also a favorable factor for improving nitrogen reduction catalytic activity. This work highlights the potential of transition metal-doped TiO2 in catalytic nitrogen reduction and provides new insights into the preparation of transition metal oxides for energy conversion applications using phase transition engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117821996B_ABST
    Figure CN117821996B_ABST
Patent Text Reader

Abstract

A transition metal M-TiO2 catalyst for efficient selective electrochemical nitrogen reduction and application thereof, tetrabutyl titanate and transition metal M salt are added into anhydrous ethanol and stirred at room temperature for 36-60 hours, wherein the molar ratio of tetrabutyl titanate, transition metal M salt and anhydrous ethanol is 6-12:0.25-1.5:430-600, then the obtained precipitate is separated, washed and dried; a transition metal M-TiO2 with X% of transition metal M weight doping amount is obtained; the transition metal M-TiO2 catalyst is obtained by annealing at 500-700 DEG C for 1.5-2.5 hours at a temperature increasing rate of 5 DEG C·min ‑1 -1 in air. The transition metal element doped TiO2 can induce phase change engineering, and the doped TiO2 produces more abundant oxygen vacancies, so that the electrochemical reduction of nitrogen to ammonia under ambient conditions can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemistry, and in particular to a highly efficient and selective electrochemical nitrogen reduction method using Fe doping to regulate the phase transition and defects of TiO2. Background Technology

[0002] Ammonia plays an important role as a chemical feedstock in the production of chemical products such as fertilizers and industrial fuels, due to its high hydrogen content (17.6 wt%) and energy density (4.32 kWh / h). -1 Ammonia is also an important carrier of clean energy. The traditional Haber-Bosch process, which produces ammonia under high temperature and pressure, emits large amounts of greenhouse gases. Electrocatalytic nitrogen reduction, with its advantages of low energy consumption, controllable reaction, simple equipment, and sustainability under environmental conditions, is widely considered a highly attractive method. Noble metals exhibit high catalytic activity for electrocatalytic nitrogen reduction, but their high cost, scarce resources, and hydrogen evolution reaction severely limit their large-scale application. Therefore, developing efficient non-noble metal nitrogen reduction catalysts is an urgent task, but it remains a significant challenge.

[0003] Titanium-based materials, due to their stronger affinity for nitrogen atoms than for hydrogen atoms, show great potential in the electrocatalytic reduction of nitrogen. TiO2, as a typical n-type semiconductor, has been widely used in catalysis due to its biocompatibility, chemical stability, and abundant availability. However, TiO2 also suffers from poor conductivity and a limited number of active sites. Summary of the Invention

[0004] The primary objective of this invention is to develop a catalyst with high reduction rate and metal doping-modified TiO2; The second objective of this invention is to provide a catalyst application system for metal-doped TiO2 with high efficiency and selective electrochemical nitrogen reduction.

[0005] To achieve the objective of this invention, a transition metal M-TiO2 catalyst for efficient and selective electrochemical nitrogen reduction is disclosed: tetrabutyl titanate and a transition metal M salt are added to anhydrous ethanol and stirred at room temperature for 36–60 hours, wherein the molar ratio of tetrabutyl titanate, transition metal M salt, and anhydrous ethanol is 6–12:0.25–1.5:430–600. The resulting precipitate is then separated, thoroughly washed with deionized water and anhydrous ethanol, and vacuum dried at 30–60ºC for 6–12 hours to obtain transition metal M-TiO2 with a transition metal M weight doping amount of X%. Further in the air at 5ºC•min −1Annealing at a heating rate of 500–700°C for 1.5–2.5 hours yields a transition metal M-TiO2 catalyst, wherein the transition metal M is Fe, Mn, Co, Ni, or Cu. During the synthesis of the transition metal M-TiO2 catalyst, TiO2 is transformed into anatase structure, and transition metal M is introduced into the main structure of TiO2 in the form of metal ions; the transition metal M-TiO2 catalyst is a spherical nanoparticle structure with a size of 10-20 nm, and its nanoparticle surface exhibits a discontinuous lattice.

[0006] Furthermore, the doping amount X% of the transition metal M is 0.5% to 2.0%.

[0007] Furthermore, the transition metal M is Fe, and its doping amount X% is 1.5%.

[0008] A transition metal M-TiO2 catalyst electrode for efficient and selective electrochemical nitrogen reduction: 2 mg of the aforementioned transition metal M-TiO2 catalyst is dispersed in a mixed solution of 950 μL anhydrous ethanol and 50 μL Nafion solution, and ultrasonically treated for 20–30 minutes using an ultrasonic cleaner to form a uniform suspension; 100 μL of this suspension is dropped onto carbon paper and vacuum dried to obtain the electrode. The carbon paper is model NOS1005, 1.0 cm × 1.0 cm, manufactured by Suzhou Shengernuo Technology Co., Ltd.

[0009] Application of a transition metal M-TiO2 catalyst working electrode for efficient and selective electrochemical nitrogen reduction: Electrocatalytic nitrogen reduction tests were conducted at room temperature and pressure in an H-type electrolytic cell separated by a Nafion 115 membrane. A three-electrode system was used, with a platinum mesh electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, the Ag / AgCl electrode filled with saturated KCl solution, and the aforementioned transition metal M-TiO2 catalyst electrode serving as the working electrode. The electrolyte was a 0.1M Na2SO4 solution saturated with N2 or argon.

[0010] Furthermore, before the electrochemical experiment, the electrolyte solution needs to be bubbled with N2 or Ar for 20 to 30 minutes to saturate the N2 or Ar in the electrolyte solution.

[0011] Using the above method, oxygen vacancies and metal doping on the catalyst surface are adjusted through phase change engineering, thereby improving the electrocatalytic nitrogen reduction activity and selectivity of M-TiO2 (M=Fe, Mn, Co, Ni, Cu).

[0012] Transition metal doping of TiO2 can induce phase transition engineering, and the doped TiO2 generates more oxygen vacancies. Furthermore, catalysts prepared using heteroatom doping strategies can enhance the electrocatalytic reduction of N2 to ammonia under ambient conditions. In this patent, anatase Fe-TiO2 yielded 30.9 ± 0.4 μg h⁻¹ at a potential of -0.4 V vs. RHE. -1 mg cat. -1 High ammonia yield and high Faraday efficiency of 40.4±1.1%.

[0013] The optimized Fe1.5%-TiO2 catalyst achieved an ammonia yield of 30.9 ± 0.4 μg / h. -1 mg cat. -1 The Fe-TiO2 exhibited significant electrocatalytic nitrogen reduction performance in terms of efficiency (40.4 ± 1.1%) and Faraday efficiency (40.4 ± 1.1%), and demonstrated excellent stability over 48 hours. Experimental results show that, compared to pristine TiO2, surface oxygen vacancies and newly introduced Fe sites on the Fe-TiO2 surface effectively lower the energy barrier of the rate-determining step of nitrogen reduction, facilitating the formation of *NNH. Furthermore, after Fe doping, TiO2 underwent a phase transition to a single anatase structure, further enhancing its electrocatalytic nitrogen reduction activity. Finally, the synthesis and electrocatalytic nitrogen reduction performance of Mn-TiO2, Co-TiO2, Ni-TiO2, and Cu-TiO2 were verified. This provides a new technical solution for the chemical and physical transformation of TiO2 during phase transition processes and opens up new avenues for the design of transition metal oxides.

[0014] Density functional theory studies further demonstrate that surface oxygen vacancies and newly introduced Fe sites on the Fe-TiO2 surface can effectively lower the nitrogen reduction rate and the energy barrier of the determining step (below the energy barrier of the original TiO2), thereby promoting the catalytic performance of electrocatalytic nitrogen reduction. Fe-doped phase transition engineering, which transforms the TiO2 crystal structure into a single anatase structure, is also a favorable factor for improving nitrogen reduction catalytic activity. This work highlights the potential of transition metal-doped TiO2 in catalytic nitrogen reduction and provides new insights into the preparation of transition metal oxides for energy conversion applications using phase transition engineering. Attached Figure Description

[0015] The specific description given as a non-limiting example better explains what the invention includes and how it can be practiced. Furthermore, this description refers to the accompanying drawings, in which: Figure 1Electrochemical performance of Fe-TiO2 catalyst in 0.1 M Na2SO4 solution for nitrogen reduction. (a) Linear sweep voltammetry curves for N2 and Ar saturation; (b) Current-time curves after 1 hour of reaction at various constant potentials; (c) UV-Vis absorption spectra after 1 hour of reaction at different potentials using the indophenol blue method; (d) Ammonia yield and Faradaic efficiency after electrochemical reaction at different potentials. Figure 2 (a) NH4 at different concentrations + (a) Ultraviolet-visible absorption spectrum after color development by indophenol blue method with ionic solution; (b) Fitting curve of calibration curve; Figure 3 (a) UV-Vis absorption spectra of hydrazine (N2H4) solutions of different concentrations after Watt-Chrisp colorimetric method; (b) Fitting graph of calibration curve; Figure 4 (a) The total amount and distribution of ammonia produced in the cathode chamber, anode chamber, and tail gas absorption devices 1 and 2 after 1 hour of testing with Fe-TiO2 catalyst in N2-saturated 0.1 M Na2SO4 electrolyte at -0.40 V vs. RHE; (b) The UV-Vis absorption spectra of the solutions after Watt-Chrisp colorimetric development after 1 hour of electrochemical reaction at each constant potential; Figure 5 (a) X-ray diffraction (XRD) patterns of M-TiO2 catalysts (M = Mn, Co, Ni, Cu); (b) Ammonia yield and Faraday efficiency of M-TiO2 catalysts (M = Mn, Co, Ni, Cu); Figure 6 (a) Scanning electron microscope (SEM) image of Fe-TiO2, with the inset showing its particle size distribution; (b) Transmission electron microscope (TEM) image of Fe-TiO2; (c) High-resolution transmission electron microscope (HRTEM) image of Fe-TiO2; (d) TEM image of TiO2; (e) HRTEM image of TiO2; (fk) Elemental plane distribution map of Fe-TiO2; Figure 7 The image shows the energy dispersive spectroscopy (EDS) spectrum of Fe-TiO2. Figure 8 (a) UV-Vis absorption spectra of Fe-TiO2 catalysts prepared with different Fe doping amounts after reaction at -0.40 V vs. RHE for 1 h; (b) ammonia yield and Faraday efficiency after electrochemical reaction; (c) comparison of the function relationship between double-layer charging current and scan rate; (d) electrochemical impedance spectroscopy in N2-saturated 0.1 M Na2SO4 electrolyte. Detailed Implementation

[0016] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. Example

[0017] Synthesis of Fe-TiO2 catalyst: Tetrabutyl titanate (3 mL) and ferrous sulfate heptahydrate (0.75 mmol) were added to 30 mL of anhydrous ethanol and stirred at room temperature for 48 hours. The resulting precipitate was then separated, thoroughly washed with deionized water and anhydrous ethanol, and vacuum dried at 60ºC for 6–12 hours. Finally, it was dried in air at 5ºC•min. −1 The heating rate was set at 600ºC for annealing for 2 hours to obtain Fe-TiO2 samples with an Fe doping content (mass ratio of iron to tetrabutyl titanate) of 1.5%.

[0018] Meanwhile, under the same conditions, Fe-TiO2 samples with Fe doping amounts of 0.5%, 1.0%, 2.0%, and 2.5% were prepared by changing the amount of ferrous sulfate heptahydrate added.

[0019] Comparative Example: Synthesis of TiO2 Catalyst: TiO2 catalyst was prepared under the same conditions without the addition of ferrous sulfate heptahydrate.

[0020] The following experimental tests were conducted on a Fe-TiO2 sample with an Fe doping content of 1.5%: 1. Preparation of working electrode 2 mg of Fe-TiO2 catalyst was dispersed in a mixture of 950 μL anhydrous ethanol and 50 μL Nafion solution, and ultrasonically treated for 20 minutes using an ultrasonic cleaner to form a homogeneous suspension. 100 μL of the above suspension was dropped onto carbon paper (CeTech, NOS1005, 1.0 cm × 1.0 cm) and vacuum dried to prepare the working electrode.

[0021] The comparative TiO2 working electrode was prepared using the same method.

[0022] Electrochemical testing

[0023] Nitrogen reduction tests were conducted at room temperature and pressure in an H-type electrolytic cell separated by a Nafion 115 membrane, and the process was controlled by a Donghua DH7000 electrochemical workstation.

[0024] The test was conducted using an electrode system with a three-electrode structure, in which a platinum mesh electrode was used as the counter electrode, an Ag / AgCl electrode (filled with saturated KCl solution) was used as the reference electrode, and the carbon paper supported on the Fe-TiO2 catalyst was used as the working electrode.

[0025] The electrolyte is a 0.1 M Na2SO4 solution saturated with N2 or Ar. To ensure quality, a raw material gas purification device and a tail gas absorption device are used.

[0026] All potentials in this paper are calibrated to reversible hydrogen electrode potentials using the following formula.

[0027] Before any electrochemical experiment, the electrolyte solution should be bubbled with N2 or Ar for 20 minutes to saturate the electrolyte solution with N2 or Ar.

[0028] Example: Electrocatalytic nitrogen reduction performance test of Fe-TiO2 A series of electrochemical tests were performed in an H-type electrolytic cell using a three-electrode system. All electrochemical tests were conducted in 0.1 M Na₂SO₄ solution.

[0029] First, a linear sweep voltammetry test was performed in a 0.1 M Na₂SO₄ solution under a N₂ or Ar saturated atmosphere. For example... Figure 1 As shown in Figure a, the current density gradually increases with increasing potential. The Fe-TiO2 catalyst obtained a higher current density under N2 saturated atmosphere, which confirms the feasibility of using Fe-TiO2 for nitrogen reduction process.

[0030] Subsequently, to further evaluate the catalytic activity of the Fe-TiO2 catalyst and determine the optimal potential, the current-time curves of the Fe-TiO2 reaction at -0.3 to -0.7 V vs. RHE potentials for 1 hour were measured. Following the current-time measurements, the generated ammonia and possible byproduct hydrazine were detected using the indophenol blue method and the Watt-Chrisp method, respectively. The corresponding standard curves are shown below. Figure 2 and 3 As shown (The creation of the standard curve will be described later.)

[0031] The linear sweep voltammetry test described above was conducted in the potential range of 0.05 V vs. RHE to -0.90 V vs. RHE at a sweep rate of 5 mV / s. Current-time tests were performed at different potentials for 1 hour with a stirring rate of 200 rpm.

[0032] like Figure 1 As shown in b, the current density gradually increases with increasing potential, and remains stable during continuous testing for 1 hour, indicating that the Fe-TiO2 catalyst has good electrochemical stability.

[0033] Figure 1Figure c shows the UV-Vis absorption spectra after 1 hour of nitrogen reduction testing at different potentials. As can be seen from the figure, the highest absorption intensity was obtained at a potential of -0.4 V vs. RHE, indicating that the highest ammonia yield was obtained at this potential.

[0034] Methods for testing ammonia

[0035] Ammonia produced was determined by the indophenol blue method: First, a standard curve for ammonia was plotted: a series of standard ammonium chloride solutions of known concentrations (0, 0.2, 0.4, 0.6, 0.8, and 1.0 μg / mL) were prepared. Then, 4 mL of ammonia standard solution was taken with a pipette and 500 μL of colorimetric reagent A (a 1 mol / L sodium hydroxide aqueous solution containing 5 wt% sodium salicylate and 5 wt% trisodium citrate), 50 μL of colorimetric reagent B (a 0.05 mol / L sodium hypochlorite aqueous solution), and 50 μL of colorimetric reagent C solution (a 1 wt% sodium nitrosoferricyanide aqueous solution) were added in sequence. After 1 hour of color development, the UV-Vis absorption spectrum was measured.

[0036] like Figure 2 As shown, the fitting equation for the ammonia standard curve is y = 0.427x + 0.017, R0 2 =0.999, indicating that the standard curve has a good linear relationship. Therefore, the ammonia yield and Faraday efficiency of Fe-TiO2 material as a nitrogen reduction catalyst can be calculated based on this fitting equation.

[0037] The ammonia production in this article refers to the total ammonia collected from the cathode chamber, anode chamber, and tail gas absorption device. For the test sample in the example, 4 mL of electrolyte was transferred, and the above-mentioned colorimetric reagent was added to it sequentially. After color development for 1 hour, its ultraviolet-visible absorption spectrum was measured, the absorbance value at 663 nm was recorded, and the ammonia concentration of the corresponding test sample was calculated according to the standard curve equation.

[0038] Methods for testing hydrazine

[0039] The Watt-Chrisp method was used to assess the possible presence of hydrazine (N2H4) as a byproduct in the electrolyte.

[0040] A standard curve determination of hydrazine is required: Prepare a series of standard hydrazine solutions of known concentrations (0, 0.2, 0.4, 0.6, 0.8, and 1.0 μg / mL), using a mixture of p-dimethylaminobenzaldehyde (0.599 g), concentrated hydrochloric acid (12 mol / L, 3 mL), and anhydrous ethanol (30 mL) as the coloring reagent. Mix 2 mL of each hydrazine standard solution with 2 mL of the coloring reagent, and after 20 minutes of color development, measure the UV-Vis absorption spectrum. Figure 3 As shown, the fitting equation for the hydrazine standard curve is y = 0.669x + 0.074, R02 =0.999, indicating that the standard curve has a good linear relationship. For the test sample, 2 mL of electrolyte and 2 mL of coloring reagent were mixed, and after 20 minutes of color development, its UV-Vis absorption spectrum was measured. The absorbance value at 458 nm was recorded, and the hydrazine concentration of the corresponding test sample was calculated according to the standard curve equation.

[0041] Based on the standard curve of ammonia, the ammonia yield and Faraday efficiency at the corresponding potentials were further calculated. Figure 1 As shown in Figure d, Fe-TiO2 exhibited the best catalytic activity at a potential of -0.4 V vs. RHE, with an ammonia yield of 30.9 ± 0.4 μg h⁻¹. -1 mg cat. -1 The Faraday efficiency is 40.4 ± 1.1%, which is equivalent to or better than recently reported high-performance TiO2 and other types of nitrogen reduction electrocatalysts (as shown in Table 1 for experimental data of examples and other types of nitrogen reduction electrocatalysts on the market).

[0042] Table 1. Comparison of ammonia yield and Faraday efficiency of representative materials for electrocatalytic nitrogen reduction reaction under the same environmental conditions.

[0043] The ammonia production in this patent is the total amount of ammonia collected from the cathode chamber, anode chamber, and tail gas absorption device. For example... Figure 4 As shown in Figure a, after electrolysis for 1 hour at -0.4 V vs. RHE potential, 77.5%, 17.4%, 5.1%, and 0% ammonia were collected from the cathode chamber, anode chamber, and tail gas absorption devices 1 and 2, respectively. Furthermore, to evaluate the selectivity of nitrogen reduction products, the concentration of hydrazine as a byproduct was measured. Figure 4 The value of b indicates that no absorption peak of hydrazine was detected at each potential, which confirms the excellent selectivity of Fe-TiO2 in reducing N2 to ammonia.

[0044] Examples of methods verify the SEM and TEM characterization of Fe-TiO2 The Fe-TiO2 catalyst was characterized by SEM, TEM, and HRTEM. Figure 6 As shown in figure a, the SEM image reveals the spherical nanoparticle structure of the Fe-TiO2 sample, with a size of approximately 10–20 nm. The small size of this catalyst exposes a higher density of active sites.

[0045] Figure 6 bc are TEM and HRTEM images of the Fe-TiO2 catalyst. The TEM images show the spherical morphology of the Fe-TiO2 sample and retain the microstructure characteristics of the original TiO2. Figure 6 d). Figure 6c clearly shows that the lattice fringe spacing of Fe-TiO2 is 0.360 nm, which corresponds to the (101) crystal plane of anatase TiO2. Simultaneously, the Fe-TiO2 nanoparticles exhibit a discontinuous lattice on their surface, indicating the formation of atomic defects, which is beneficial for improving the adsorption capacity for N2 molecules. Notably, a lattice fringe spacing of 0.352 nm is clearly observed in the original TiO2 (101) plane. Figure 6 e), which is lower than the lattice fringe spacing of Fe-TiO2, consistent with subsequent XRD results.

[0046] Figure 6 fk is a high-angle annular dark-field scanning transmission electron microscope (HADDF-STEM) image of Fe-TiO2 nanoparticles and the corresponding elemental distribution map, which shows that Fe, Ti and O are uniformly distributed on the nanoparticles.

[0047] Figure 7 The EDS results also showed that Fe, Ti and O elements were present in Fe-TiO2, further proving that Fe element was successfully doped into TiO2 during the synthesis process.

[0048] The following tests were conducted on several examples of Fe-TiO2 catalysts with different Fe doping amounts, as well as comparative examples: Figure 8 The effect of Fe doping amount on the nitrogen reduction performance of Fe-TiO2 catalyst is shown. Figure 8 As shown in ab, under the same conditions, Fe-TiO2 catalysts with Fe doping amounts of 0.5% to 2.0% generally exhibit higher ammonia yield and Faradaic efficiency than the comparative TiO2 catalysts, with the Fe1.5%-TiO2 catalyst showing the highest ammonia yield and Faradaic efficiency.

[0049] like Figure 8 As shown in c, the Fe1.5%-TiO2 nanoparticles exhibit a larger double-layer capacitance, indicating that the catalyst prepared with 1.5% Fe doping can provide more reactive active sites. Furthermore, electrochemical impedance spectroscopy (EIS)... Figure 8 The results in d) indicate that the Fe1.5%-TiO2 catalyst has a lower charge transfer resistance, which means that Fe1.5%-TiO2 can provide faster electron transport efficiency. Therefore, 1.5% doping is the optimal doping amount for the Fe-TiO2 catalyst.

[0050] Electrocatalytic nitrogen reduction performance of other transition metal M-TiO2 Under the same conditions, M-TiO2 catalysts with a metal doping concentration of 1.5% were prepared by using the following transition metal sulfates instead of ferrous sulfate heptahydrate. The XRD results are shown below. Figure 5 As shown in Figure a, M-TiO2, like Fe-TiO2, underwent a phase transition, exhibiting only anatase structure. This indicates that the synthesis method is universal for TiO2 phase transitions induced by transition metal doping. Next, the nitrogen reduction performance of the M-TiO2 catalysts (M = Mn, Co, Ni, Cu) was tested at -0.4 V vs. RHE potential. Figure 5 b). The results show that these metal-doped catalysts achieved higher ammonia yields and Faradaic efficiencies than the original TiO2, further demonstrating that TiO2 materials prepared by metal element doping synthesis methods can improve electrocatalytic nitrogen reduction performance.

[0051] In the embodiments, the electrochemical active surface area of ​​Fe-TiO2 catalysts with different Fe doping amounts was measured by double-layer capacitance method, and cyclic voltammetry was used for testing, with scan rates of 100, 150, 200, 250 and 300 mV / s, respectively.

[0052] Electrochemical impedance spectroscopy was performed in N2-saturated 0.1 M Na2SO4 electrolyte, with a frequency range from 10000 Hz to 0.1 Hz.

[0053] The above embodiments and illustrations are not intended to limit the product form and style of the present invention. Any appropriate changes and modifications made by those skilled in the art should be considered as not departing from the patent scope of the present invention.

Claims

1. A transition metal M-TiO2 catalyst for highly efficient and selective electrochemical nitrogen reduction, characterized in that: Tetrabutyl titanate and transition metal M salt were added to anhydrous ethanol and stirred at room temperature for 36–60 hours, wherein the molar ratio of tetrabutyl titanate, transition metal M salt, and anhydrous ethanol was 6–12:0.25–1.5:430–600. The resulting precipitate was then separated, thoroughly washed with deionized water and anhydrous ethanol, and vacuum dried at 30–60ºC for 6–12 hours to obtain transition metal M-TiO2 with a transition metal M weight doping amount of X%; wherein the transition metal M doping amount X% is 0.5%–2.0%. Further in the air at 5ºC•min −1 Annealing at a heating rate of 500–700°C for 1.5–2.5 hours yields a transition metal M-TiO2 catalyst, wherein the transition metal M is Fe, Mn, Co, Ni, or Cu. During the synthesis of the transition metal M-TiO2 catalyst, TiO2 is transformed into anatase structure, and transition metal M is introduced into the main structure of TiO2 in the form of metal ions; the transition metal M-TiO2 catalyst is a spherical nanoparticle structure with a size of 10-20 nm, and its nanoparticle surface exhibits a discontinuous lattice.

2. The transition metal M-TiO2 catalyst for highly efficient and selective electrochemical nitrogen reduction as described in claim 1, characterized in that: The transition metal M is Fe, and its doping amount X% is 1.5%.

3. A transition metal M-TiO2 catalyst electrode for efficient and selective electrochemical nitrogen reduction, characterized in that: 2 mg of the transition metal M-TiO2 catalyst according to any one of claims 1 to 2 is dispersed in a mixed solution of 950 μL anhydrous ethanol and 50 μL Nafion solution, and ultrasonically treated for 20 to 30 minutes using an ultrasonic cleaner to form a uniform suspension; 100 μL of the suspension is dropped onto carbon paper and vacuum dried to obtain an electrode.

4. An application of a transition metal M-TiO2 catalyst working electrode for efficient and selective electrochemical nitrogen reduction, characterized in that: Electrocatalytic nitrogen reduction was tested at room temperature and pressure in an H-type electrolytic cell separated by a Nafion 115 membrane. An electrode system with a three-electrode structure was used for the test, in which a platinum mesh electrode was used as the counter electrode, an Ag / AgCl electrode was used as the reference electrode, the Ag / AgCl electrode was filled with saturated KCl solution, and the electrode of claim 3 was used as the working electrode; the electrolyte was a 0.1M Na2SO4 solution saturated with N2 or argon.

5. The application of the working electrode of the transition metal M-TiO2 catalyst for efficient and selective electrochemical nitrogen reduction as described in claim 4, characterized in that: Before electrochemical experiments, the electrolyte solution needs to be bubbled with N2 or Ar for 20 to 30 minutes to saturate the electrolyte solution with N2 or Ar.

Citation Information

Patent Citations

  • Preparation method of fuel cell hydroxide non-platinum catalyst

    CN107275653A

  • Metal M-doped titanium dioxide photocatalyst and application thereof in photocatalytic nitrogen fixation

    CN112642427A